2018
DOI: 10.1515/hf-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of decay in creosote-treated Scots pine poles in Ireland

Abstract: Air-seasoning is a simple method for moisture management in utility poles prior to treatment, but it involves the risk of fungal invasion during drying. These fungi can be eliminated by heat treatment, but fungi surviving in the installed poles are a quality problem. In this context, the incidence of decay fungi was investigated in 963 creosote-treated Scots pine (Pinus sylvestris) poles of varying ages in a utility system in Ireland. Thirty-seven percent of increment cores removed from the poles contained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, ascomycete molds such as Penicillium or Aspergillus tend to predominate in isolation studies unless steps are taken to minimize their growth. The isolates were identified by isolation and amplification of DNA as previously described (Cappellazzi et al 2018). Cultures of the test fungi were maintained on 1,5 % malt extract agar until needed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, ascomycete molds such as Penicillium or Aspergillus tend to predominate in isolation studies unless steps are taken to minimize their growth. The isolates were identified by isolation and amplification of DNA as previously described (Cappellazzi et al 2018). Cultures of the test fungi were maintained on 1,5 % malt extract agar until needed.…”
Section: Methodsmentioning
confidence: 99%
“…Potential decay fungi were segregated by growth morphologies as well as the presence of hyphal clamp connections and septa. Pure sub-cultured morphogroups were subjected to conservative DNA identification where multiple isolates of each morphogroup were sequenced (Cappellazzi et al 2018). Fungal DNA was extracted from pure-culture vegetative mycelium using the cetyl trimethylammonium bromide (CTAB) protocol (Gardes and Bruns 1993) with minor modification.…”
Section: Methodsmentioning
confidence: 99%
“…Fungal DNA amplification, sequencing, and processing were performed exactly as described in Cappellazzi et al (2018). Briefly, the internal transcribed spacer region of fungal rDNA was amplified from morphologically unique isolates using the fungal specific forward primer ITS1F (5′-CTTGGTCATTTAGAGGAAGTAA-3′) (Gardes and Bruns 1993) and the general eukaryotic reverse primer ITS4 (5′TCCTCCGCTTATTGATATGC-3′) (White et al 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have theorized [49,50] that woody biomass is to some extent "pre-wired" for deterioration based on the assemblages of tree-associated saprophytes that persist in the standing tree that are not eliminated during primary processing [51]. This has received limited attention in lumber but was discussed in recent work by Cappellazzi et al [52], who found that latent fungal opportunists persisted even in creosote treated utility poles that were not subjected to pre-sterilization methods. These studies could potentially explain the observed dissimilarity of the soil and wood assemblages, particularly the 61 basidiomycete OTUs that were specific to wood.…”
Section: Soil and Wood Have Distinctly Different Basidiomycete Commun...mentioning
confidence: 99%